Investigation on particulate emissions and combustion characteristics of a common-rail diesel engine fueled with Moringa oleifera biodiesel-diesel blends - Teoh, Yew Heng; How, Heoy Geok; Masjuki, Haji Hassan; Nguyen, H.-T.; Kalam, Md. Abul; Alabdulkarem, Abdullah (Elsevier, 2019)
In this study, a study of the effects of Moringa Oil Biodiesel (MOB) biodiesel-diesel blends on the engine's performance, exhaust particulate matter, gaseous emissions and combustion characteristics was carried out in a multi-cylinder high-pressure common-rail diesel engine. The experiment involved the use of baseline diesel and several MOB blends (MOB10, MOB20, MOB30 and MOB50) as the fuel for the diesel engine. The results concluded that the engine torques and brake power produced by all of the MOB blends is smaller to the baseline diesel. However, both the MOB blends and baseline diesel produced similar brake thermal efficiency (BTE). It is noticed that the brake specific fuel consumption (BSFC) of all MOB are indicating deterioration, but showing an improvement in the brake specific energy consumption (BSEC). Besides, the peak cylinder pressure and peak HRR indicated a trend of declination with the increasing biodiesel blend ratio. Furthermore, all MOB has shown a great improvement in the emission of carbon monoxide (CO), smoke and particulate matter (PM), except nitrogen oxides (NOx). In short, Moringa oil is suitable to use as a source of biodiesel fuel in the diesel engines without any engine modification needs to be done. © 2019 Elsevier Ltd